Preparation method of metal soft magnetic core with high magnetic conductance and low loss
By using weak organic acids and high temperature resistant silicone resin for passivation and coating, combined with annealing treatment, the problems of low magnetic permeability and high loss in the prior art are solved, and efficient and simple preparation of metal soft magnetic cores are achieved. Magnetic performance and process efficiency are significantly optimized.
Patent Information
- Application Number
- CN202411152457.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing metal soft magnetic powder core preparation process, phosphoric acid passivation and organic coating have problems such as excessive acidification and high temperature failure, resulting in low magnetic permeability, high loss, and complex process, long time and high energy consumption.
Weak organic acids are used as passivating agents to passivate the metal soft magnetic powder, and surface coating is used with high-temperature resistant silicone resin, combined with annealing treatment to form a magnetic core with high magnetic permeability and low loss. Specific steps include: mixing and stirring the metal soft magnetic powder with organic weak acid and volatile solvent, adding high-temperature resistant silicone resin and solvent to mix and stir, removing the solvent and pressing and forming, and performing vacuum or protective atmosphere annealing.
The preparation of metal soft magnetic cores with high permeability and low loss is achieved. The process is simple, time-consuming, low energy consumption, simple and efficient operation, and controllable acidification strength, forming a uniform and dense passivation layer, improving the surface pole Improves the coating effect.
Smart Images

Figure BDA0005004026080000071 
Figure BDA0005004026080000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal soft magnetic cores, and in particular relates to a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. Background Art
[0002] The main preparation process of metal soft magnetic powder core is to first passivate and coat the metal soft magnetic powder, and then press it into shape with a mold; the current conventional soft magnetic metal powder preparation process includes metal soft magnetic powder screening, passivation, insulation coating, pressing, curing annealing and other processes. The main purpose of metal soft magnetic particle coating is to achieve insulation between particles, thereby reducing eddy current loss between metal magnetic powder core particles; the quality of the insulation coating layer determines the quality of its high-frequency magnetic properties and losses.
[0003] Currently, commonly used insulating coatings include passivation + organic coating / inorganic coating and other processes. The passivation process mainly uses phosphoric acid as a solvent to perform surface passivation treatment on the soft magnetic alloy powder, forming an inorganic layer on the surface of the powder to achieve an insulating effect. The organic coating process mainly uses materials such as epoxy resin, phenolic resin or silicone resin to mix the soft magnetic alloy powder and form an organic layer on its surface to achieve bonding and insulation. However, the current conventional phosphoric acid passivation and organic coating have problems of excessive acidification and high-temperature failure, resulting in the pain points of low magnetic permeability and high loss in the magnetic properties of the magnetic powder core.
[0004] In order to solve the above problems, the conventional passivation + organic coating / inorganic coating has been improved in the prior art, such as using a method of resin coating followed by acid passivation, adding oxides and clay substances to the passivator in addition to acidic substances, and then assisting with complex heat treatment processes to improve magnetic permeability and reduce losses. However, the above methods have cumbersome reagent types, complex operations, long time consumption, and high energy consumption.
[0005] In view of this, a method is needed that has a simple process and can prepare a metal soft magnetic core with high magnetic permeability and low loss. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a method for preparing a metal soft magnetic core with high magnetic permeability and low loss, aiming to solve at least one technical problem in the background technology.
[0007] The present invention is achieved in that:
[0008] The present invention provides a method for preparing a metal soft magnetic core with high magnetic permeability and low loss, the preparation method comprising:
[0009] Using organic weak acid as a passivating agent to passivate the metal soft magnetic powder;
[0010] adding an organic coating solvent to coat the surface of the passivated soft magnetic metal powder to form a soft magnetic metal powder with an organic coating layer;
[0011] Pressing the metal soft magnetic powder into a shape to obtain a magnetic core;
[0012] Annealing the magnetic core to obtain the metal soft magnetic core with high magnetic permeability and low loss;
[0013] Wherein, the organic coating solvent is a high temperature resistant silicone resin.
[0014] Furthermore, the organic weak acid is oxalic acid.
[0015] Furthermore, the specific operation of the passivation is:
[0016] Mix the metal soft magnetic powder with organic weak acid and volatile solvent, and stir them fully in a non-vacuum closed environment;
[0017] The volatile solvent is evaporated and removed, and then sieved to obtain the passivated metal soft magnetic powder;
[0018] The amount of the organic weak acid used is 1% to 3% of the weight of the metal soft magnetic powder.
[0019] Furthermore, the amount of the organic weak acid used is 1% to 1.5% of the weight of the metal soft magnetic powder.
[0020] Furthermore, the specific operation of surface coating is:
[0021] The passivated soft magnetic metal powder is mixed with a high temperature resistant silicone resin and a solvent, and stirred fully in a non-vacuum closed environment;
[0022] After removing the solvent, the powder is sieved to obtain a metal soft magnetic powder with a particle size of 80 to 150 meshes;
[0023] Wherein, the amount of high temperature resistant silicone resin is 1% of the weight of the metal soft magnetic powder;
[0024] The high temperature resistant silicone resin adopts a silicone resin containing a phenyl group.
[0025] Furthermore, the annealing treatment is carried out in a vacuum or protective atmosphere; the temperature of the annealing treatment is 700° C. to 750° C., and the time is 1 h to 2 h.
[0026] Furthermore, the passivation and the surface coating are both carried out at 25°C to 40°C.
[0027] Furthermore, the metal soft magnetic powder adopts at least one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder.
[0028] Furthermore, the particle size of the metallic soft magnetic powder is not greater than 200 meshes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention adopts organic acid for passivation and combines it with special high-temperature silicone resin coating, which avoids the problem of high-temperature failure, thereby making the coating effect better and the loss can be significantly optimized. In addition, the present invention produces a high-permeability, low-loss metal soft magnetic core based on a simple coating process.
[0031] 2. The present invention dilutes the passivation material and the organic coating material with a volatile solvent, and the passivation layer and the coating layer can be prepared by stirring. The raw materials are simple and easy to obtain, and the reaction conditions are mild. It takes less time and energy, and the operation is simple and efficient, which is conducive to industrial production.
[0032] 3. The acidification intensity of the present invention can be controlled with high precision, thereby forming a uniform, dense and ultra-thin passivation layer on the surface of the metal powder, with better powder passivation effect and consistent product performance.
[0033] 4. The present invention adopts organic acid coating. After acidification, a large number of organic molecular chains exist, which improves the surface polarity of the metal soft magnetic powder and is conducive to the effective coating of the subsequent silicone resin.
[0034] 5. The weakly acidic organic acid used in the present invention can reduce the damage to operators and equipment. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] A method for preparing a metal soft magnetic core with high magnetic permeability and low loss comprises the following steps:
[0037] (1) Use organic weak acid as a passivating agent to passivate the metal soft magnetic powder;
[0038] The metal soft magnetic powder is mixed with an organic weak acid and a volatile solvent, and stirred fully in a non-vacuum closed environment at a temperature of 25°C to 40°C for about 12 minutes; the volatile solvent is evaporated and then sieved to obtain the passivated metal soft magnetic powder;
[0039] Specifically, the metal soft magnetic powder can be made of soft magnetic materials permitted in the art, including but not limited to at least one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder, and the particle size of the metal soft magnetic powder is not higher than 200 meshes; the following embodiments use Fe-Si alloy powder, Fe-Si-Al alloy powder and the like as examples, but are not limited to these materials, and other unlisted metal soft magnetic powders are also applicable;
[0040] In the present invention, organic acid coating is adopted to form a uniform, dense and ultra-thin passivation layer on the surface of the metal soft magnetic powder; and a large number of organic molecular chains exist in the passivation layer formed after acidification, thereby improving the surface polarity of the metal soft magnetic powder and providing favorable contact for the subsequent coating of high temperature resistant silicone resin; in the present invention, oxalic acid is adopted as the organic weak acid, and the amount of the organic weak acid is 1% to 3% of the weight of the metal soft magnetic powder;
[0041] In this step, the volatile solvent is ethanol, which dilutes the organic weak acid, so that the formation of the passivation layer is faster, more efficient and more evenly distributed. During the volatilization process, it can be heated to a certain temperature to accelerate the volatilization and dry the powder.
[0042] (2) adding an organic coating solvent to coat the surface of the passivated soft magnetic metal powder to form a soft magnetic metal powder having an organic coating layer;
[0043] The passivated soft magnetic metal powder is mixed with a high temperature resistant silicone resin and a solvent (xylene), and stirred in a non-vacuum sealed environment at a temperature of 25°C to 40°C for about 12 minutes; heated to about 80°C and low temperature dried for about 1 hour, and sieved after removing the solvent to obtain a soft magnetic metal powder with a particle size of 80 mesh to 150 mesh;
[0044] Conventional silicone resins are prone to cracking and failure at high temperatures, resulting in poor high-frequency performance and increased losses. The high-temperature resistant silicone resin (such as TSR 145) used in the present invention achieves high temperature resistance by introducing phenyl groups and a unique silicon-oxygen bond structure. In the molecular structure of the silicone resin, the introduction of phenyl groups can effectively improve its high temperature resistance. This is because the conjugated structure of the phenyl group can provide additional stability to prevent the resin from cross-linking or degradation at high temperatures. The bond energy of the silicon-oxygen (Si-O-Si) bond is relatively high, at approximately 444 kJ / mol, which is much higher than the bond energy of the carbon-carbon (CC) bond (approximately 348 kJ / mol). This makes the silicone resin have higher thermal stability at high temperatures and is not easily decomposed or degraded.
[0045] In a specific implementation, the amount of the high temperature resistant silicone resin is 1% of the weight of the metal soft magnetic powder; the organic coating solvent uses a high temperature resistant silicone resin, specifically, the high temperature resistant silicone resin uses a silicone resin containing a phenyl group, such as methylphenyl silicone resin, methylphenyl vinyl silicone resin, etc. The following embodiment selects methylphenyl silicone resin as an example, but is not limited to this material, and other silicone resins containing phenyl groups are also applicable;
[0046] The purpose of sieving in steps (1) and (2) is mainly to increase the fluidity of the powder and avoid agglomeration, which would affect subsequent coating and magnetic core pressing.
[0047] (3) pressing the metal soft magnetic powder into a shape to obtain a magnetic core;
[0048] The soft magnetic metal powder treated in step (2) is placed in a mold and pressed at 2100 MPa for several seconds to obtain a magnetic core. The specification and model can be selected according to actual needs. In the following embodiment, two specifications and sizes of 270 and 330 are selected for illustration;
[0049] 270 and 330 refer to conventional specifications and models defined in the art according to the outer diameter of the magnetic core. In the present invention, 270 refers to OD*ID*HT=26.92*14.73*11.18; 330 refers to OD*ID*HT=30.02*19.9*10.67.
[0050] (4) annealing the magnetic core to obtain the metal soft magnetic core with high magnetic permeability and low loss;
[0051] Annealing is performed in a vacuum or protective atmosphere at a temperature of 700°C to 750°C for 1 hour to 2 hours; the protective atmosphere may be conventional gases such as nitrogen and / or argon to form a non-oxygen environment;
[0052] Specifically, the annealing temperature and time may be adjusted according to the type of the metallic soft magnetic powder.
[0053] Example 1
[0054] This embodiment prepares a metal soft magnetic core with high magnetic permeability and low loss, and the preparation method thereof includes the following steps:
[0055] (1) Weigh 100 g of 200-mesh Fe-Si-Al alloy soft magnetic powder, add 1% oxalic acid and 3% ethanol by weight of the soft magnetic powder, and stir thoroughly for 12 min at room temperature in a non-vacuum closed space; heat to about 80° C. and dry at low temperature for about 1 h, and pass through an 80-mesh sieve after the ethanol is completely evaporated;
[0056] (2) adding a mixed solution of 1% by weight of the soft magnetic powder of methylphenyl silicone resin and 3% by weight of xylene solvent to the powder obtained in step (1), stirring the mixture in a non-vacuum closed space for 12 minutes, heating the mixture to about 80° C. and drying the mixture at low temperature for about 1 hour, and filtering the mixture through an 80-mesh sieve after the xylene solvent is completely evaporated to obtain an alloy Fe-Si-Al powder granulation material having a particle size range of 80-150 mesh;
[0057] (3) The above alloy Fe-Si-Al powder granules are placed in a mold and pressed at 2100 MPa for several seconds to obtain a soft magnetic composite magnetic powder core (specification: 270).
[0058] (4) The molded magnetic core is annealed at 750°C in vacuum for 1 hour to obtain a metallic soft magnetic core.
[0059] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0060] Example 2
[0061] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and embodiment 1 lies in the amount of oxalic acid used in step (1). This embodiment uses 1.5% oxalic acid, and the remaining steps and parameters are the same as those in embodiment 1.
[0062] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0063] Example 3
[0064] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and embodiment 1 lies in the amount of oxalic acid used in step (1). This embodiment uses 3% oxalic acid, and the remaining steps and parameters are the same as those in embodiment 1.
[0065] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0066] Example 4
[0067] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and embodiment 1 lies in the model of the magnetic core in step (3). The specification of the magnetic core in this embodiment is 330, and the remaining steps and parameters are the same as those in embodiment 1.
[0068] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0069] Example 5
[0070] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and Example 2 lies in the model of the magnetic core in step (3). The specification of the magnetic core in this embodiment is 330, and the remaining steps and parameters are the same as those in Example 2.
[0071] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0072] Example 6
[0073] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and Example 3 lies in the model of the magnetic core in step (3). The specification of the magnetic core in this embodiment is 330, and the remaining steps and parameters are the same as those in Example 3.
[0074] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0075] Example 7
[0076] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and embodiment 1 lies in the type of metal soft magnetic powder in step (1). At the same time, the degradation temperature is adjusted to 700°C due to the different types of powders. This embodiment uses Fe-Si alloy soft magnetic powder, and the remaining steps and parameters are the same as those in embodiment 1.
[0077] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0078] Example 8
[0079] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and Example 2 lies in the type of metal soft magnetic powder in step (1). This embodiment uses Fe-Si alloy soft magnetic powder, and the remaining steps and parameters are the same as those in Example 2.
[0080] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0081] Example 9
[0082] This embodiment is a method for preparing a metal soft magnetic core with high magnetic permeability and low loss. The difference between this embodiment and Example 3 lies in the type of metal soft magnetic powder in step (1). This embodiment uses Fe-Si alloy soft magnetic powder, and the remaining steps and parameters are the same as those of Example 3.
[0083] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the method of this embodiment were tested at different frequencies and magnetic field intensities. The results are shown in Table 1.
[0084] Comparative Example 1
[0085] This comparative example is a method for preparing a metal soft magnetic core. The difference between it and Example 1 lies in the acid used for passivation in step (1) and the type of silicone resin used in step (2). In this comparative example, phosphoric acid is used in step (1) and methyl silicone resin is used in step (2). The remaining steps and parameters are the same as those in Example 1.
[0086] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0087] Comparative Example 2
[0088] This comparative example is a method for preparing a metal soft magnetic core. The difference between it and Example 2 lies in the acid used for passivation in step (1) and the type of silicone resin used in step (2). In this comparative example, phosphoric acid is used in step (1) and methyl silicone resin is used in step (2). The remaining steps and parameters are the same as those in Example 2.
[0089] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0090] Comparative Example 3
[0091] This comparative example is a method for preparing a metal soft magnetic core. The difference between it and Example 7 lies in the acid used for passivation in step (1) and the type of silicone resin used in step (2). In this comparative example, phosphoric acid is used in step (1) and methyl silicone resin is used in step (2). The remaining steps and parameters are the same as those in Example 7.
[0092] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0093] Comparative Example 4
[0094] This comparative example is a method for preparing a metal soft magnetic core. The difference between it and Example 8 lies in the acid used for passivation in step (1) and the type of silicone resin used in step (2). In this comparative example, phosphoric acid is used in step (1) and methyl silicone resin is used in step (2). The remaining steps and parameters are the same as those in Example 8.
[0095] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0096] Comparative Example 5
[0097] This comparative example is a method for preparing a metal soft magnetic core. The difference between this comparative example and Example 1 is that the acid used for passivation in step (1) is phosphoric acid, and the remaining steps and parameters are the same as those in Example 1.
[0098] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0099] Comparative Example 6
[0100] This comparative example is a method for preparing a metal soft magnetic core. The difference between this comparative example and Example 1 lies in the type of silicone resin used in step (2). In this comparative example, step (2) uses methyl silicone resin, and the remaining steps and parameters are the same as those in Example 1.
[0101] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0102] Comparative Example 7
[0103] This comparative example is a method for preparing a metal soft magnetic core. The difference between it and Example 1 lies in the acid used for passivation in step (1). In step (1) of this comparative example, a composite acid of inorganic acid (phosphoric acid) + organic acid (oxalic acid) is used as a passivating agent, specifically 0.5% phosphoric acid + 0.5% oxalic acid. The remaining steps and parameters are the same as those in Example 1.
[0104] The inductance, magnetic permeability and loss performance of the metal soft magnetic core prepared by the comparative example method under different frequencies and magnetic field intensities were tested, and the results are shown in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] The inductance L is measured at 100KHz / 1v.
[0109] The difference between Examples 1 to 3 is only the amount of oxalic acid (1% to 3%). It can be seen from the data in Table 1 that with the increase in the amount of oxalic acid, the losses at 50kHZ / 50mT, 100kHZ / 50mT, and 100kHZ / 100mT all decrease, and the loss at 50kHZ / 100mT first increases and then decreases; however, the inductance and permeability also decrease with the increase in the amount of oxalic acid, and the decrease in inductance and permeability is smaller when the oxalic acid is 1% to 1.5%. The difference between Examples 4 to 6 and Examples 7 to 9 is the amount of oxalic acid, and the transformation trend of their overall performance is roughly the same as that of Examples 1 to 3, so the increase in the amount of oxalic acid can reduce the loss, but it will affect the inductance and permeability. The preferred content is 1% to 1.5%, which has less negative impact on inductance and magnetic permeability. The organic acid is combined with the high-temperature silicone resin, and the desired magnetic permeability requirement can be achieved through the controllable acidification of the organic acid.
[0110] The difference between Example 1 and Example 4, Example 2 and Example 5, and Example 3 and Example 6 is only the type of magnetic core. It can be seen from Table 1 that the combination of oxalic acid+high temperature resistant organic resin of the present invention is applicable to different types of magnetic cores.
[0111] The only difference between Example 1 and Example 7, Example 2 and Example 8, and Example 3 and Example 9 is the type of metal soft magnetic powder. It can be seen from Table 1 that the effect of the combination of oxalic acid + high temperature resistant organic resin on the magnetic core performance of the present invention is applicable to different types of metal soft magnetic powder raw materials.
[0112] The difference between Comparative Example 1 and Example 1, Comparative Example 2 and Example 2, Comparative Example 3 and Example 7, and Comparative Example 4 and Example 8 is that the materials of the passivation layer and the resin coating layer are different; it can be seen from the data in Table 1 that compared with the corresponding embodiments, the inductance of the comparative example is reduced by 177.96% to 376.44%, the magnetic permeability is reduced by 178.54% to 375.32%, and the loss at different frequencies and different magnetic field strengths is increased by 12.67% to 46.02%.
[0113] The difference between Comparative Example 5 and Example 1 is that a single phosphoric acid is used as the passivation layer material, and the difference between Comparative Example 6 and Example 1 is that a conventional resin is used as the coating layer material. It can be seen from the data in Table 1 that compared with Example 1, the inductance of Comparative Example 5 is reduced by 243.22%, the magnetic permeability is reduced by 244.01%, and the loss at different frequencies and magnetic field intensities is increased by 5.97% to 24.78%; compared with Example 1, the inductance of Comparative Example 6 is reduced by 257.43%, the magnetic permeability is reduced by 257.81%, and the loss difference is not significant.
[0114] In Comparative Example 7, a phosphoric acid + oxalic acid composite material is used as a passivation layer material. It can be seen from the data in Table 1 that, compared with Example 1, the inductance of Comparative Example 7 is reduced by 266.22%, the magnetic permeability is reduced by 266.40%, and the loss at different frequencies and different magnetic field intensities is increased by 37.73% to 47.07%; from the comparison of Comparative Examples 5 and 7 with Example 1, it can be seen that using a single organic weak acid (oxalic acid) as a passivator, the product magnetic core performance is much better than the magnetic core performance obtained by passivation with a single inorganic acid (phosphoric acid) and a composite passivation of an inorganic acid (phosphoric acid) + an organic acid (oxalic acid).
[0115] In summary, compared with the traditional process, the product after coating and annealing by the present invention not only has higher magnetic permeability, but also has more advantages in reducing losses.
[0116] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a metal soft magnetic core with high magnetic permeability and low loss, characterized in that: The preparation method comprises: Using organic weak acid as a passivating agent to passivate the metal soft magnetic powder; adding an organic coating solvent to coat the surface of the passivated soft magnetic metal powder to form a soft magnetic metal powder with an organic coating layer; Pressing the metal soft magnetic powder into a shape to obtain a magnetic core; Annealing the magnetic core to obtain the metal soft magnetic core with high magnetic permeability and low loss; Wherein, the organic coating solvent is a high temperature resistant silicone resin.
2. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1, characterized in that: The organic weak acid is oxalic acid.
3. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1 or 2, characterized in that: The specific operation of the passivation is: Mix the metal soft magnetic powder with organic weak acid and volatile solvent, and stir them fully in a non-vacuum closed environment; The volatile solvent is evaporated and removed, and then sieved to obtain the passivated metal soft magnetic powder; The amount of the organic weak acid used is 1% to 3% of the weight of the metal soft magnetic powder.
4. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 3, characterized in that: The amount of the organic weak acid used is 1% to 1.5% of the weight of the metal soft magnetic powder.
5. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1, characterized in that: The specific operation of the surface coating is: The passivated soft magnetic metal powder is mixed with a high temperature resistant silicone resin and a solvent, and stirred fully in a non-vacuum closed environment; After removing the solvent, the powder is sieved to obtain a metal soft magnetic powder with a particle size of 80 to 150 meshes; Wherein, the amount of high temperature resistant silicone resin is 1% of the weight of the metal soft magnetic powder; The high temperature resistant silicone resin adopts a silicone resin containing a phenyl group.
6. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1, characterized in that: The annealing treatment is carried out in a vacuum or protective atmosphere; the temperature of the annealing treatment is 700° C. to 750° C., and the time is 1 hour to 2 hours.
7. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1, characterized in that: The passivation and the surface coating are both carried out at 25°C to 40°C.
8. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1, characterized in that: The metal soft magnetic powder is at least one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder.
9. The method for preparing a metal soft magnetic core with high magnetic permeability and low loss according to claim 1, characterized in that: The particle size of the metal soft magnetic powder is not greater than 200 meshes.
Citation Information
Patent Citations
Method for preparing amorphous soft magnetic powder core
CN103730225A
Method for preparing iron-silicon-aluminum soft magnetic powder core through warm-pressing
CN105344993A
Method for assisting insulation coating of magnetic powder by organic acid passivation solution
CN118136394A
Boron- and silicon-coated metal soft magnetic powder core and preparation method therefor
WO2024088426A1
